2002
DOI: 10.2165/00007256-200232010-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Scientific Basis for High-Intensity Interval Training

Abstract: While the physiological adaptations that occur following endurance training in previously sedentary and recreationally active individuals are relatively well understood, the adaptations to training in already highly trained endurance athletes remain unclear. While significant improvements in endurance performance and corresponding physiological markers are evident following submaximal endurance training in sedentary and recreationally active groups, an additional increase in submaximal training (i.e. volume) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
305
1
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 691 publications
(376 citation statements)
references
References 166 publications
14
305
1
12
Order By: Relevance
“…Improvements in body fat percentage were also noted; males incurred an average decrease of 4.2% while females experienced a 3.4% decrease. This finding is similar to investigations of other forms of high-intensity interval-type training and resistance exercise-based circuit training that have resulted in improved measures of fitness (Laursen & Jenkins, 2002). Franch et al (Franch, Madsen, Djurhuus, & Pedersen, 1998) showed that 6 weeks of intense interval training using 4 to 6 sets of 4 minute intervals resulted in a 6% improvement in VO2max and a greater increase in time to exhaustion at 85% VO2max compared to 6 weeks of continuous running (+93% vs. +67%, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…Improvements in body fat percentage were also noted; males incurred an average decrease of 4.2% while females experienced a 3.4% decrease. This finding is similar to investigations of other forms of high-intensity interval-type training and resistance exercise-based circuit training that have resulted in improved measures of fitness (Laursen & Jenkins, 2002). Franch et al (Franch, Madsen, Djurhuus, & Pedersen, 1998) showed that 6 weeks of intense interval training using 4 to 6 sets of 4 minute intervals resulted in a 6% improvement in VO2max and a greater increase in time to exhaustion at 85% VO2max compared to 6 weeks of continuous running (+93% vs. +67%, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…Parallel with earlier findings [10,11,14], this study reported that high-intensity aerobic training is effective for improving VO 2max in cross-country skiers. It can be advantageous for endurance performance to slightly reduce intensity and use longer duration of intervals in endurance athletes [10].…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have reported that similar effects of aerobic high-intensity endurance training on performance and aerobic characteristics [14]. Parallel with earlier findings [10,11,14], this study reported that high-intensity aerobic training is effective for improving VO 2max in cross-country skiers.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have reported that similar effects of aerobic high-intensity endurance training on performance and aerobic characteristics [19]. Parallel with earlier findings [12,15,19], it can be said that high-intensity aerobic interval training has significant effects on VO2max in crosscountry skiers. With the start of using the skating technique, importance of upper body anaerobic capacity stated by several studies [10,22].…”
Section: Discussionsupporting
confidence: 63%